1991
DOI: 10.1089/dna.1991.10.663
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Fragment Fingerprint and Genome Sizes ofStaphylococcusSpecies Using Pulsed-Field Gel Electrophoresis and Infrequent Cleaving Enzymes

Abstract: Large restriction fragments of genomic DNA from Staphylococcus species were separated by pulsed-field gel electrophoresis (PFGE). Five different strains of S. aureus (ISP8, SAU3A, PS96, ATCC 6538, ATCC 15564) and three representative strains of S. haemolyticus SM102, S. warneri MCS4, S. cohnii LK478 from human hosts, and one strain of S. aureus (ATCC 8432) from an avian host were used in this study. Since Staphylococcus is A + T rich (approximately 67%), restriction fragments were obtained by digesting chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although there are biochemical and serological methods for species-specific discrimination among the staphylococci, methods for strain specific identification are needed for the accurate tracking of the epidemics and for conducting traceback studies. The molecular typing methods used to characterize staphylococci include ribotyping [15] and PFGE [13,16]. We used our modification of a PFGE method [13] to examine the genomic relatedness of 15 outbreak-associated isolates, which represented patient and food sources from both states involved.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are biochemical and serological methods for species-specific discrimination among the staphylococci, methods for strain specific identification are needed for the accurate tracking of the epidemics and for conducting traceback studies. The molecular typing methods used to characterize staphylococci include ribotyping [15] and PFGE [13,16]. We used our modification of a PFGE method [13] to examine the genomic relatedness of 15 outbreak-associated isolates, which represented patient and food sources from both states involved.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Ichiyama et al identified 3 1 restriction patterns amongst 1 1 1 isolates of methicillin-resistant S. aureus by their SmaI digestion pattern^.^ In this study the changes in the types of S . aureus colonising the human nasal cavity were followed for > 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…14 Increased resistance or susceptibility to several common poultry diseases, including tibial dyschondroplasia, Marek's disease, Rous sarcoma, and cecal coccidiosis, has been unequivocally linked to certain MHC genotypes. 9, 12, 16, 23, 25 In addition, MHC associations with moderately and highly pathogenic strains of S. aureus have been described in White Leghorn chickens. 8 Albeit, staphylococcosis and MHC associations have not been established in broiler breeder chickens.…”
mentioning
confidence: 99%